2013
DOI: 10.1016/s0254-6272(13)60146-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical treatment of myasthenia gravis with deficiency of spleen and kidney based on combination of disease with syndrome theory

Abstract: Using the theory on the combination of disease with syndrome, we found that the curative effect of Jianjining and Western Medicine on MG patients with deficiency of both spleen and kidney is worth further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Meta-analysis of three studies (Ou, 2005; Niu, 2009; Lai, 2013) showed that CHMs paratherapy were significant for decreasing MG clinical absolute and relative score ( n = 156, MD −2.36, 95% CI: −3.10 to −1.61, p < 0.00001; heterogeneity χ 2 = 1.53, df = 2, p = 0.47, I 2 = 0%, Figure 4 ) compared to pyridostigmine bromide and corticosteroids; one (Ju, 2003) study also have positive result compared with corticosteroids ( p < 0.01); three studies (Barohn et al, 1998; Bao, 2016; Bao et al, 2016) failed to pool analysis because of high heterogeneity and all showed statistical significant difference compared with pyridostigmine bromide ( p < 0.01). Meta-analysis of four studies (Ou, 2005; Niu, 2009; Lai, 2013; Shuang and Tan, 2014) showed CHMs paratherapy significantly improved the total clinical effective rate ( n = 194, RR 1.05, 95% CI: 0.99–1.12, p = 0.11; heterogeneity χ 2 = 0.79, df = 3, p = 0.85, I 2 = 0%, Figure 5 ) compared with pyridostigmine bromide and corticosteroids; two studies (Ju, 2003; Zu, 2015) are similar result ( n = 90, RR 1.06, 95% CI: 0.94–1.20, p = 0.34; heterogeneity χ 2 = 0.16, df = 1, p = 0.69, I 2 = 0%) compared with corticosteroids; five studies (Wang et al, 2008; Liang, 2011; Jiang et al, 2014; Bao, 2016; Bao et al, 2016) failed to pool analysis because of high heterogeneity and all showed statistical significant difference compared with pyridostigmine bromide ( p < 0.01). Meta-analysis of five studies (Ju, 2003; Xu et al, 2004; Wang et al, 2008; Liang, 2011; Lai, 2013) showed that CHMs paratherapy were significant for improving the relapse rate after follow-up ( n = 291, OR 0.22, 95% CI: 0.11–0.48, p = 0.0001; heterogeneity χ 2 = 0.77, df = 4, p = 0.94, I 2 = 0%, Figure 6 ) compared WCM controls.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Meta-analysis of three studies (Ou, 2005; Niu, 2009; Lai, 2013) showed that CHMs paratherapy were significant for decreasing MG clinical absolute and relative score ( n = 156, MD −2.36, 95% CI: −3.10 to −1.61, p < 0.00001; heterogeneity χ 2 = 1.53, df = 2, p = 0.47, I 2 = 0%, Figure 4 ) compared to pyridostigmine bromide and corticosteroids; one (Ju, 2003) study also have positive result compared with corticosteroids ( p < 0.01); three studies (Barohn et al, 1998; Bao, 2016; Bao et al, 2016) failed to pool analysis because of high heterogeneity and all showed statistical significant difference compared with pyridostigmine bromide ( p < 0.01). Meta-analysis of four studies (Ou, 2005; Niu, 2009; Lai, 2013; Shuang and Tan, 2014) showed CHMs paratherapy significantly improved the total clinical effective rate ( n = 194, RR 1.05, 95% CI: 0.99–1.12, p = 0.11; heterogeneity χ 2 = 0.79, df = 3, p = 0.85, I 2 = 0%, Figure 5 ) compared with pyridostigmine bromide and corticosteroids; two studies (Ju, 2003; Zu, 2015) are similar result ( n = 90, RR 1.06, 95% CI: 0.94–1.20, p = 0.34; heterogeneity χ 2 = 0.16, df = 1, p = 0.69, I 2 = 0%) compared with corticosteroids; five studies (Wang et al, 2008; Liang, 2011; Jiang et al, 2014; Bao, 2016; Bao et al, 2016) failed to pool analysis because of high heterogeneity and all showed statistical significant difference compared with pyridostigmine bromide ( p < 0.01). Meta-analysis of five studies (Ju, 2003; Xu et al, 2004; Wang et al, 2008; Liang, 2011; Lai, 2013) showed that CHMs paratherapy were significant for improving the relapse rate after follow-up ( n = 291, OR 0.22, 95% CI: 0.11–0.48, p = 0.0001; heterogeneity χ 2 = 0.77, df = 4, p = 0.94, I 2 = 0%, Figure 6 ) compared WCM controls.…”
Section: Resultsmentioning
confidence: 84%
“…Meta-analysis of four studies (Ou, 2005; Niu, 2009; Lai, 2013; Shuang and Tan, 2014) showed CHMs paratherapy significantly improved the total clinical effective rate ( n = 194, RR 1.05, 95% CI: 0.99–1.12, p = 0.11; heterogeneity χ 2 = 0.79, df = 3, p = 0.85, I 2 = 0%, Figure 5 ) compared with pyridostigmine bromide and corticosteroids; two studies (Ju, 2003; Zu, 2015) are similar result ( n = 90, RR 1.06, 95% CI: 0.94–1.20, p = 0.34; heterogeneity χ 2 = 0.16, df = 1, p = 0.69, I 2 = 0%) compared with corticosteroids; five studies (Wang et al, 2008; Liang, 2011; Jiang et al, 2014; Bao, 2016; Bao et al, 2016) failed to pool analysis because of high heterogeneity and all showed statistical significant difference compared with pyridostigmine bromide ( p < 0.01). Meta-analysis of five studies (Ju, 2003; Xu et al, 2004; Wang et al, 2008; Liang, 2011; Lai, 2013) showed that CHMs paratherapy were significant for improving the relapse rate after follow-up ( n = 291, OR 0.22, 95% CI: 0.11–0.48, p = 0.0001; heterogeneity χ 2 = 0.77, df = 4, p = 0.94, I 2 = 0%, Figure 6 ) compared WCM controls.…”
Section: Resultsmentioning
confidence: 84%
“…The Qi-supplementing Formula group consisted of 882 patients, while the WM treatment group consisted of 809 patients. Of the WM treatments, 4 trials [14, 24, 30, 32] used only cholinesterase inhibitors, 7 trials [13, 15, 16, 22, 26, 27, 29, 33] applied immunosuppressants alone, 10 trials [12, 17–21, 23, 25, 28, 31] used cholinesterase inhibitors in combination with immunosuppressants simultaneously, and 1 trial [34] used two types of immunosuppressants. The course of treatment ranged from 1 to 24 months.…”
Section: Resultsmentioning
confidence: 99%
“…Six trials [16, 21, 23, 29, 31, 33] were randomized using random number tables to generate a sequence (appropriate), two trials [28, 32] used a temporal sequence for randomization (inappropriate), and the remaining trials only mentioned randomization without detailed methods. Three trials [21, 25, 31] were randomized controlled placebo designs. One trial [21] reported the blinding of outcome assessments, and one trial [34] reported the patients' reasons for withdrawal or loss to follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation